2021
DOI: 10.1016/j.atherosclerosis.2021.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of cardiac troponin in hospitalized COVID-19 patients

Abstract: Background and aim Myocardial injury defined by elevation of cardiac troponins (cTn) in the course of coronavirus disease 2019 (COVID-19) pandemic has been reported, though not fully characterized yet. Using the Turkish nationwide centralized COVID-19 database, we sought to determine whether cTn measured within 24 hours of admission may help identify 30-day all-cause mortality in hospitalized patients. Methods This retrospective cohort study was conducted at all hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…After adjusting for multiple variables (e.g., age, pre-existing cardiovascular diseases, cerebrovascular diseases, diabetes mellitus, chronic obstructive pulmonary disease, renal failure, cancer, ARDS, creatinine levels, and NT-proBNP levels), the hazard ratio (HR) for death among patients with cardiac injury was 4.26 (95% CI, 1.92–9.49), p < 0.01 ( 39 ). The prognostic role of cardiac injury was confirmed in further and larger studies from different countries (including European, American, and Asiatic nations), with mortality HR ranging from 1.12 to 8.9 depending on the regression model used and OR up to 80 in a single univariate model ( 17 , 71 82 ) ( Table 3 ). Data from a recent meta-analysis including 12,262 patients from 13 studies summarized that elevated Tn is associated with increased mortality (OR, 4.75; 95% CI, 4.07–5.53; p < 0.001; I 2 = 19.9%), with 55% sensitivity and 80% specificity ( 83 ).…”
Section: Subclinical Acute Myocardial Injury In Covid-19mentioning
confidence: 69%
See 3 more Smart Citations
“…After adjusting for multiple variables (e.g., age, pre-existing cardiovascular diseases, cerebrovascular diseases, diabetes mellitus, chronic obstructive pulmonary disease, renal failure, cancer, ARDS, creatinine levels, and NT-proBNP levels), the hazard ratio (HR) for death among patients with cardiac injury was 4.26 (95% CI, 1.92–9.49), p < 0.01 ( 39 ). The prognostic role of cardiac injury was confirmed in further and larger studies from different countries (including European, American, and Asiatic nations), with mortality HR ranging from 1.12 to 8.9 depending on the regression model used and OR up to 80 in a single univariate model ( 17 , 71 82 ) ( Table 3 ). Data from a recent meta-analysis including 12,262 patients from 13 studies summarized that elevated Tn is associated with increased mortality (OR, 4.75; 95% CI, 4.07–5.53; p < 0.001; I 2 = 19.9%), with 55% sensitivity and 80% specificity ( 83 ).…”
Section: Subclinical Acute Myocardial Injury In Covid-19mentioning
confidence: 69%
“…Since the first Chinese reports, a high incidence of cardiac injury, defined as the presence of elevated troponin (Tn) levels above the 99th percentile of the reference interval, was found in COVID-19 patients. The prevalence of cardiac injury ranges from 12% in unselected COVID-19 cases up to 41% in critically ill patients and patients with pre-existing cardiovascular diseases with a further rise to 75.8% in nonsurvivors (Table 3) (14,17,18,24,25,38,39,(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82). The presence of elevated Tn levels is associated with abnormal laboratory findings (including white blood cells count, neutrophil and lymphocyte count, C-reactive protein, procalcitonin, Nterminal pro-B-type natriuretic peptide, D-dimer, transaminases, lactate dehydrogenase, total bilirubin, albumin, prothrombin time, and cytokines) (18) and a higher grade of pulmonary involvement in radiographic findings, suggesting an important multiorgan involvement (21,38,73).…”
Section: Subclinical Acute Myocardial Injury In Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…Till now, the predictive value of myocardial injury in patients with COVID-19 during the in-hospital term or short term is mixed. A series of studies have shown that myocardial injury in patients with COVID-19 is very common and associated with higher mortality ( 12 22 ). However, other studies indicated that the influence of myocardial injury is attenuated after adjusting multiple severe diseases ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%